Ceramic microchannel reactors with channel sizes less than 100 μm prepared by a mesh-assisted phase-inversion process. Issue 18 (15th September 2021) - Zhao, Zhibo; Ma, Yuyao; Sun, Wenguang; Ye, Zhengmao; Zhao, Weilin; Buckley, C.E.; Dong, Dehua
Abstract: Microchannel reactors show fast mass transfer and heat transfer while limited active surface area, which can be greatly increased by reducing channel sizes. However, conventional extrusion makes honeycomb ceramics with channel sizes above 100 μm. This study has prepared ceramic microchannel reactors with channel sizes in the range of 1–100 μm by a one-step phase-inversion process, and channels are formed through the convection between coagulant and solvent. The effect of channel size on reaction performance was investigated by comparing two reactors with different channel sizes in dry reforming of methane. In addition, the microstructure of the reactors can be further tuned via sintering temperature to achieve high catalytic performance owing to the balanced active surface and mass transfer. Therefore, the microchannel reactors developed in this study represent a diagram-shift in the preparation of microchannel reactors by making channels with sizes less than 100 μm, which has potential applications in many catalytic reactions.